Kierkegaard’s Ethics as an Answer to Human Alienation in Technocratic Society - Roman Kralik; Susanne Jakobsen Tinley (Communications - Scientific letters of the University of Zilina, 2017)
Kierkegaard is well-known for his noting tendencies of the present age which point in the direction of alienation. Tracking the course of Danish society’s moral trajectory Kierkegaard considers recent developments in the direction of the outward, the superficiality of a mindset that craves entertainment and the latest fad. This hunger for entertainment, epitomized by the technical marvels of Tivoli, leaves man on the outside, a spectator unable to make important decisions. Whereas Kierkegaard’s emphasis on the individual encountered in the critique of ‘the crowd’ can, and has been seen as an indirect critique of democracy (echoing Plato’s objections) it is a concern with any potential threat to the integrity of the individual. Considering Kierkegaard in relation to other dominant voices of his time we find that he is concerned not only with the pastimes of his fellow citizens but more precisely with the lack of an overall idea of the true nature of human existence, a deficiency leaving them prey to technocratic encroachments.